Scoliosis in a Case of Schinzel–Giedion Syndrome - Sharma, Amit K. (Springer-Verlag, 2009)
Schinzel–Giedion syndrome (SGS) is a rare disorder characterized by midface retraction, hypertrichosis, and multiple skeletal anomalies with severe mental retardation. Various skeletal manifestations of the disease have been previously described. We present the first case of SGS developing scoliosis. The patient presented with scoliosis at the age of 8 years which rapidly progressed to severe thoraco-lumbar scoliosis. Survival beyond 2 years is rare in this syndrome. The objective of this report is to describe the possibility of development of scoliosis in SGS due to the neuromuscular nature of the syndrome, especially in long survivors.